Development of a thinking actively in a social context (TASC)-based digital worksheet ecosystem (DWE) to improve creative thinking ability - Henny Iriantini; Diana Vivanti Sigit; Rizhal Hendi Ristanto (Master Program of Biology Education, Universitas Lambung Mangkurat, Banjarmasin, Indonesia, 2026)
Digital Worksheet Ecosystem (DWE) based on Tasc (Thinking Actively In Social Context) was developed as an innovative learning media to facilitate understanding of ecosystem material interactively and contextually. This study aims to develop DWE and analyze its feasibility and influence on students' creative thinking skills. The research method uses the Hannafin and Peck development model consisting of needs analysis, design, and development and implementation, followed by evaluation and revision at each stage. The results of expert validation showed that DWE is very valid and feasible to use as a biology learning media. The results of the test percentage of creative thinking skills in the experimental class and the highest control class in the ability of flexible thinking indicators (experimental), the experimental class at 98.5% and the control class at 90.5%, while in the experimental class the lowest value on the original thinking indicator (originality ) equal to 55.00% and the control class on the original thinking indicator (originality) of 46.5%. The results showed that the average value of the ability to think creatively in the experimental class scored 76.94 while the control class scored 68.02. The implementation of DWE showed a significant improvement in students' creative thinking skills in terms of fluency, flexibility, originality, and elaboration. These findings indicate that TASC-based DWE is effective in improving students' creative thinking skills in biology learning.Abstrak. Ekosistem Lembar Kerja Digital (DWE) yang didasarkan pada Tasc (Berpikir Aktif dalam Konteks Sosial) dikembangkan sebagai media pembelajaran inovatif untuk memfasilitasi pemahaman materi ekosistem secara interaktif dan kontekstual. Penelitian ini bertujuan untuk mengembangkan DWE dan menganalisis kelayakan serta pengaruhnya terhadap keterampilan berpikir kreatif siswa. Metode penelitian menggunakan model pengembangan Hannafin dan Peck yang terdiri dari analisis kebutuhan, desain, pengembangan, dan implementasi, diikuti dengan evaluasi dan revisi pada setiap tahap. Hasil validasi ahli menunjukkan bahwa DWE sangat valid dan layak digunakan sebagai media pembelajaran biologi. Hasil persentase kemampuan berpikir kreatif pada kelas eksperimen dan kelas kontrol tertinggi dalam indikator kemampuan berpikir fleksibel (eksperimen), kelas eksperimen sebesar 98,5% dan kelas kontrol sebesar 90,5%, sementara pada kelas eksperimen nilai terendah pada indikator pemikiran asli (originalitas) sebesar 55,00% dan kelas kontrol pada indikator pemikiran asli (originalitas) sebesar 46,5%. Hasil menunjukkan bahwa nilai rata-rata kemampuan berpikir kreatif di kelas eksperimen sebesar 76,94 sementara kelas kontrol sebesar 68,02. Penerapan DWE menunjukkan peningkatan yang signifikan dalam keterampilan berpikir kreatif siswa dalam hal kelancaran, fleksibilitas, keaslian, dan elaborasi. Temuan ini menunjukkan bahwa DWE berbasis TASC efektif dalam meningkatkan keterampilan berpikir kreatif siswa dalam pembelajaran biologi.